ANALISIS PENDAPATAN INDUSTRI TAHU (Studi Kasus pada Industri Rumah Tangga Tahu “KALKID” di Desa Kalitinggar Kidul Kabupaten Purbalingga) - Ayu Sitanini (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2023)
This study aims to identify the tofu processing industry in Kalitinggar Kidul village, Purbalingga district and determine the income level from the production of tofu "KALKID" in Kalitinggar Kidul village, Padamara, Purbalingga district. This study is a type of descriptive study using a quantitative research method that can be represented by numbers that describe and analyze the tofu producers increasing their sales. Based on the description of the research results and the analysis that has been done, it shows that the technology used is still traditional, but the manufacturers process the soybeans to make tofu very clean, which can be a good example. for other tofu industries. and the waste generated from processing soybeans into tofu is sold to beef farmers. Domestic Tofu Industry Sales Analysis "KALKID" achieved a turnover of Rp 28,561,000 in 4 months from October 2022 to March 2023. The business run by tofu maker "KALKID" has been profitable so far, so it's worth continuing. This is demonstrated by the magnitude of the RCR value greater than 1 (one).